Age of peak competitive performance of elite athletes: A systematic review - Allen, S. V.; Hopkins, W. G. (Sports Medicine, 2015)
Knowledge of the age at which elite athletes achieve peak performance could provide important information for long-term athlete development programmes, event selection and strategic decisions regarding resource allocation. Objectives